Evolution of Peruvian gynecology up to the Bicentennial, and the future - Rechkemmer Prieto, Adolfo (2021)
A brief overview of the evolution of gynecology in Peru in the last 200 years is done. Following the medicine and surgery practiced by the inhabitants in the pre-Hispanic era, known through their huacos and archeological sites, and after the development of diagnostic and operative gynecology with the systematic use of the speculum in the 19th century, which made possible interventions such as uterine curettage and posterior colpotomy for the drainage of pelvic abscesses, the history of Peruvian gynecology would begin in 1878, when Lino Alarco performed the first gynecological surgery by laparotomy to remove an ovarian tumor. Néstor Corpancho, in his service at the Hospital de Santa Ana, was the first to perform myomectomies by laparotomy, as well as hysterectomies. In 1879, the Chair of Gynecology was created in the Faculty of Medicine of the Universidad Nacional Mayor de San Marcos, and later the first modern operating room was installed in Peru. In 1898, Constantino T. Carvallo initiated the training of brilliant gynecologists, which was later continued with the schooling of specialists and access to updated medical information. For health outcomes resulting from the COVID-19 pandemic, greater investment in health, construction and implementation of hospitals, training of skilled professionals with a focus on emergencies and person-centered health will be required. Gynecologists will need to increase their research on women’s health in the country, their diseases and timely prevention, and deepen their knowledge in genetics, immunology, fertility and infertility, metabolic syndrome and related comorbidities (obesity, hypertension, diabetes mellitus), prolonging the healthy lives of women with differentiated care and the use of nanotechnology, artificial intelligence and robotics.